Transhepatic Insertion of Percutaneous Endoscopic Gastrostomy Tube - Zaid Imam; C. Roberto Simons-Linares (Case Reports in Gastrointestinal Medicine)
Inadvertent injury to interposing organs during percutaneous endoscopic gastrostomy (PEG) tube placement is a feared complication of this common and generally safe procedure. Transhepatic PEG insertion is likely an underrepresented complication which may be identified incidentally on imaging or present with life-threatening conditions such as sepsis or massive bleeding. Use of ultrasound in patients with known hepatomegaly may possibly help avoid this complication. We hereby report a case of transhepatic PEG insertion, one of 16 only other cases published in the literature, and review the characteristics of the previous reported cases.